Intellectual Portrait Gallery: Agusto Fauni Espiritu's Five Faces of Exile - Burns, Gerald (Archīum Ateneo, 2024)
Espiritu writes a book which may be described as a “collective intellectual biography” of five figures in Philippine letters whose lives and texts were influenced by their expatriation in America: Carlos P. Romulo, Carlos Bulosan, Jose Garcia Villa, N.V.M. Gonzalez, and Bienvenido Santos. With a biographer’s touch, Espiritu identifies the themes that are more or less common and played out differently among them: performativity, ambivalence, nationalism in their self-representation, cultural hybridity, and patronage relations—leading to what may be called a genuine “transnational” perspective for Asian American intellectual history. However, his use of other big terms such as “exile,” “nation,” “Filipino” and “Filipino-American,” and “intellectual” raises questions and provokes discussions that may yet inform our reading of these critical biographies.